2013
DOI: 10.3748/wjg.v19.i27.4596
|View full text |Cite
|
Sign up to set email alerts
|

Impact of being overweight on the surgical outcomes of patients with gastric cancer: A meta-analysis

Abstract: This meta-analysis demonstrates that a high BMI not only increases the surgical difficulty and complications but also impairs the long-term survival of patients with gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
38
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 49 publications
3
38
1
2
Order By: Relevance
“…Due to the high rate of comorbidities, obesity is frequently considered to represent a major risk factor for complications after surgery. Previous reports have identified postoperative complications correlating with a high BMI [4,15,17] . However, with regard to colorectal carcinoma, it was shown that a high BMI does not affect oncologic outcomes after surgery [18] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the high rate of comorbidities, obesity is frequently considered to represent a major risk factor for complications after surgery. Previous reports have identified postoperative complications correlating with a high BMI [4,15,17] . However, with regard to colorectal carcinoma, it was shown that a high BMI does not affect oncologic outcomes after surgery [18] .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, patients lose weight after gastrectomy to the extent that they begin to suffer from malnutrition [10,11] . Although a low BMI has been thought to be associated with a better short-term outcome than a high BMI due to simplicity and steadiness of surgical procedure [4] , the long-term outcome in low-BMI patients has remained unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are published studies that have investigated the relationship between BMI and complications, the results of these studies have been inconsistent [5][6][7]14]. Moreover, in their meta-analysis, Wu et al [15] demonstrated that obesity only increased the risk of postoperative complications and prolonged the duration of hospitalization, but obesity did not affect the total number of excised lymph nodes. Intra-operational time, the need for blood transfusions, and the number of excised lymph nodes were determined to be surgical challenges within the scope of our study; no differences, however, were found among the groups.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity has generally been regarded as a poor prognostic factor for the intraoperative and postoperative outcomes following gastric cancer 2,3) . One of the reasons for this is higher local recurrence because complete lymph node dissection is difficult in gastric cancer patients with obesity 2,4) .…”
mentioning
confidence: 99%